2007
DOI: 10.1159/000105551
|View full text |Cite
|
Sign up to set email alerts
|

Non-Cardiovascular Mortality, Low-Density Lipoprotein Cholesterol and Statins: A Meta-Regression Analysis

Abstract: Background: As of today, the effect of statins on non-cardiovascular mortality is still being debated. Single studies have not been able to provide definite answers. We performed a meta-regression analysis on randomized statin trials in order to provide evidence that non-cardiovascular mortality is related to statin treatment and low-density lipoprotein (LDL) cholesterol plasma level. Methods: We selected 29 randomized controlled trials of statins versus placebo, a total of 90,480 patients, with a follow-up of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 95 publications
0
7
0
Order By: Relevance
“…Second, epidemiological studies suggest that low LDL-C in the oldest old may exert an indirect effect to increase non-cardiovascular mortality [4]. It was not possible to establish a direct link of low LDL-C to an adverse effect on vascular mortality or non-vascular mortality because of the unavailable cause-specific mortality in our study.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Second, epidemiological studies suggest that low LDL-C in the oldest old may exert an indirect effect to increase non-cardiovascular mortality [4]. It was not possible to establish a direct link of low LDL-C to an adverse effect on vascular mortality or non-vascular mortality because of the unavailable cause-specific mortality in our study.…”
Section: Discussionmentioning
confidence: 69%
“…First, studies of older populations have led to conflicting conclusions on the relationship between LDL-C and all-cause mortality. Some studies showed that high concentrations of LDL-C were associated with higher risk of mortality and morbidity of cardiovascular and cerebrovascular diseases or all-cause mortality among the elderly [2, 3], while other studies found that low LDL-C concentrations were associated with increased mortality risk from non-cardiovascular disease [4], such as cancer [5], infection [6], liver diseases [7], and trauma [8] among elderly. Several studies also concluded that LDL-C was inversely associated with the risk of death in elderly people [914], which has attracted particular attention regarding the necessity for LDL-C lowering therapy in the aged population.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that overall mortality was significantly lower in groups treated with a statin than placebo, independent of the statin lipid-lowering effect. 39 Several reports have also indicated that statins possess antioxidant effects that are thought to help reduce overall mortality. 40 We showed that statin treatment helped to decrease the free m1A level in CKD patients.…”
Section: Trna Degradation Affords a Prognosis That Allows Interventionmentioning
confidence: 99%
“…Another study finds a trend of increased noncardiovascular mortality with decreased LDL, in both placebo and treatment groups (Razzolini et al 2008). However, at each given LDL cholesterol level, noncardiovascular mortality is lower in patients treated with statins (Razzolini et al 2008).…”
Section: Cholesterol and Infectionmentioning
confidence: 98%
“…Conversely, studies of younger adults reveal that the effect of total cholesterol on noncardiovascular mortality is neutral (Kronmal et al 1993;Krumholz et al 1994;Gould et al 1995). Another study finds a trend of increased noncardiovascular mortality with decreased LDL, in both placebo and treatment groups (Razzolini et al 2008). However, at each given LDL cholesterol level, noncardiovascular mortality is lower in patients treated with statins (Razzolini et al 2008).…”
Section: Cholesterol and Infectionmentioning
confidence: 99%